The California Privacy Rights Act (CPRA) - An implementation and compliance guide - Bukaty, Preston (ITpro collection., 2021)
The California Privacy Rights Act (CPRA) - An implementation and compliance guide is essential reading. Not only does it serve as an introduction to the legislation, it also discusses the challenges a business may face when trying to achieve CPRA compliance.